PENERAPAN MODEL DISCOVERY LEARNING BERBASIS MOBILE VIRTUAL LABORATORY UNTUK MENINGKATKAN KETERAMPILAN PROSES SAINS DASAR - Li'isyatin Hidah; Elok Sudibyo (Jurusan IPA, Fakultas Matematika dan Ilmu Pengetahuan Alam, Universitas Negeri Surabaya, 2022)
This study aimed to describe the effectiveness application model discovery learning -based mobile virtual laboratory on simple aircraft material to improving student’s basic science process skills, learning implementation and student response questionnaires. The type of research was pre-experimental with one group pretest posttest as the design. The research subjects were students of grade VIII I SMPN 16 Surabaya totaling 39 students. The research instruments were in the form of test sheets for basic science process skills, observation sheets for the implementation of discovery learning, and student response questionnaire sheets. Data collection techniques were carried out using test, observation, and questionnaire methods. The data analysis technique uses quantitative descriptive. The implementation of learning both the first and second meetings obtained percentage of 93.75%-100% with each meeting included very good category. There is increase in basic science process skills in terms of the average pretest and posttest results of 45.38 to 83.21 with classical completeness on the posttest 94.87% and the acquisition N-gain score of 0.70 which included in the medium category. In the student response questionnaire for all statement items including very good category of the average student response answers are in the interval above 3.41 to 4.21 from the highest scale worth 5. The conclusion is learning with the model discovery learning based on mobile virtual laboratory can improve basic science process skills and get a positive response from students.